Immunogenetic factors involved in the progression to Aids - Fernandes, Ana Paula M.; Gonçalves, Maria Alice G.; Gir, Elucir; Donadi, Eduardo A. (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Acquired immunodeficiency syndrome (Aids) is a disease characterizcd by the progression towards opportunistic infections and neoplasia due to the Progressive acquired immunosuppression after Human Immunodeficiency Vinis (HlV) infection. The variety of temporal pattems from the initiation of HIV infection to the progression of aids make us believe in the hypothesis of severa! factors involved in the development of the disease. Genelic factors. such as Human Leukocyte Antigen (HLA) have been associated with rapid or slow progression of the disease. and may be utilized as immunogenetic markcrs in order to predict the evolution of the disease.